Implementasi Kebijakan Program Aktivasi Kepesertaan PBPU BP PEMDA / KIS PBI D UHC Guna Meningkatkan Pelayanan Kesehatan MBR Kabupaten Sidoarjo - Aiga Putri Mawaddah R; Endan Indartuti; Dida Rahmadanik (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze and describe the PBPU BP PEMDA/KIS PBI D UHC activation program policy to improve health services for low-income communities in Sidoarjo Regency. This type of research uses qualitative descriptive research, with data collection techniques carried out through observation and interviews. This research uses the theory of George Edward III. The research results explain that the PBPU BP PEMDA/KIS PBI D UHC activation program to improve health services, especially for low-income communities in the Sidoarjo Regency area, has been quite effective overall, but there are still several obstacles that can still be overcome by improvement and re-evaluation. The implementation of the PBPU BP PEMDA/KIS PBI D UHC activation program to improve health services for low-income communities in Sidoarjo Regency is expected to improve the quality of services better in the future..